Clinical trials on diabetic nephropathy: a cross-sectional analysis - Modafferi, Sergio; Ries, Markus; Schmitt, Claus P.; Nawroth, Peter Paul; Kopf, Stefan; Peters, Verena (Diabetes therapy, 2019)
IntroductionTreatment options and decisions are often based on the results of clinical trials. We have evaluated the public availability of results from completed, registered phase III clinical trials on diabetic nephropathy and current treatment options.MethodsThis was a cross-sectional analysis in which STrengthening the Reporting of OBservational studies in Epidemiology criteria were applied for design and analysis. In June 2017, 34 completed phase III clinical trials on diabetic nephropathy in the ClinicalTrials. gov registry were identified and matched to publications in the ClinicalTrials.gov registry and to those in the PubMed and Google Scholar databases. If no publication was identified, the principal investigator was contacted. The ratio of published and non-published studies was calculated. Various parameters, including study design, drugs, and comparators provided, were analyzed.ResultsDrugs/supplements belonged to 26 different categories of medications, with the main ones being angiotensin-converting enzyme inhibitors, angiotensin-II receptors blockers, and dipeptidyl-peptidase-4-inhibitors. Among the trials completed before 2016 (n = 32), 22 (69%) were published, and ten (31%) remained unpublished. Thus, data on 11 different interventions and more than 1000 patients remained undisclosed. Mean time to publication was 26.5 months, which is longer than the time constrictions imposed by the U.S. Food and Drug Administration Amendments Act. Most trials only showed weak effects on micro- and macroalbuminuria, with an absolute risk reduction of 1.0 and 0.3%, respectively, and the number needed to treat varied between 91 and 333, without any relevant effect on end-stage-renal disease by intensive glucose-lowering treatment. Comparison of the results, however, was difficult since study design, interventions, and the renal outcome parameters vary greatly between the studies.ConclusionDespite the financial and human resources involved and the relevance for therapeutic guidelines and clinical decisions, about one-third of phase III clinical trials on diabetic nephropathy remain unpublished. Interventions used in published trials showed a low efficacy on renal outcome.FundingDeutsche Forschungsgemeinschaft (DFG): SFB 1118.
Gesehen am 29.03.2019